Leaf Anatomy of some Species in the Genera Miliusa, Mitrephora, Polyalthia and Sageraea (Annonaceae: Miliuseae) in Thailand - ปิยะประภาพันธ์ เกื้อชน; ศรีนวล อนิษฐาน (KKU Science Journal, 2015)
The leaf anatomy of four genera and 15 species in the tribe Miliuseae (Annonaceae) were investigated including four species each of Miliusa and Mitrephora, six species of Polyalthia and one species of Sageraea. Permanent slides of leaf epidermis were prepared by epidermal peeling and stained with 1% safranin in water while transverse section of leaf blade and petiole were prepared by paraffin method using a sliding microtome and stained with 1% safranin and 1% fast green in 95% ethanol and examined using light microscope. Anatomical characteristics were described. Photographs were taken with an Olympus DP 12 digital camera fitted with the microscope. The results indicated that the significant leaf anatomical characteristics for species identification are 1) shapes and characteristics of anticlinal cell wall of epidermal cells of leaf blade, 2) types and distribution of stomata, 3) the presence, types and distribution of trichomes on leaf blade and petiole, 4) number of palisade layers in leaf blade, 5) types and distribution of crystals in leaf blade and petiole, 6) shape of petiole in transverse section and 7) types of cells in the cortex of petiole.